SC-based control architectures for EMC - Titarenko, L. A.; Barkalov, A. A. (ХНУРЕ, 2023)
Two new architectures are discussed which targets at implementing LUT-based circuits of control units. Each of them leads to different circuit of Mealy finite state machine. Depending on characteristics of an FSM, one of these approaches provides minimum LUT count. The methods target FSM providing control for electromagnetic compatibility of radiotechnical devices.
Keywords: radiotechnical devices